Systematic review of the literature and meta-analysis of the long-term likelihood of contralateral total hip arthroplasty - Jonas Liebe; Michel Schläppi; Christoph Meier; Peter Wahl (EFORT Open Reviews)
Purpose: Total hip arthroplasty (THA) is performed commonly for various end-stage diseases of the hip joint. However, the likelihood of a subsequent contralateral THA (cTHA) after primary unilateral index THA (iTHA) remains insufficiently defined, with reported rates of 13–29.1% after 5 years and 8.7–54% after 10 years of follow-up. This review aims to determine the long-term likelihood over time of cTHA after iTHA. Methods: Systematic review of the literature with meta-analysis, including any clinical study published until July 2022, evaluating or documenting the likelihood over time of cTHA after iTHA, independently of the etiology. Excluded were cTHA within 12 months. A total of 21 studies, including 1,456,071 patients, who subsequently received 249,117 cTHA, were analyzed. Kaplan–Meier analysis was performed, weighting data on sample size, considering death as competing risk. Results: At 5 years after iTHA, likelihood of cTHA was 17.8% (95% confidence interval 12.3–23.3%). At 10 years, this likelihood increased to 22.7% (16.1–29.4%), with a marginal subsequent increase. The likelihood increased slightly considering death as competing risk. Conclusion: Nearly every fourth THA patient will require cTHA within 10 years. The likelihood of cTHA in this review appears to fall within the lower third of previously published ranges. However, most cTHA are required within the first years. Our findings suggest that the likelihood of requiring cTHA within the initial 10 years is approximately twice as high as the likelihood of requiring revision of the iTHA.